STRUCTURAL ANALYSIS OF THE PASSENGER NT-60 BOGIE WAGON BOGIE TYPE - Yusron, Rifky; Bisono, Rahayu; Aziz R , M. Shafwallah Al.; Arifin , Agus Choirul (Jurnal Rekayasa Mesin, 2025)
The welded bogie railway was typically exposed to very intricate fatigue loads, resulting in a significant risk of failure. However, most standards only took into account external excitations from wheel-rail system when evaluating fatigue performance. NT-60 was a common bogie train fleet in Indonesia because it manufactured in the only company then supply to the largest train operator in Indonesia. The 2x3 general linear model factorial was applied as design of experiment, load tests and static test was set as independent variable, each loading had three levels: 18, 19, and 20 tons was conducted in three replications. Strain of bogie were detected using strain gauge type LY-11 and stress using linear variable displacement transducer, all set on load test bogie tester machine. This research focuses on knowing the load type and load variables bogie to displaying which variables affect the stress on the bogie, whereas previous research only focused on the stress results caused by the load. Factorial design of experiments provided a detailed characterization of strain and stress under varying load conditions, delivering an accurate and systematic approach to show relationship between stress and strain. The lowest average strain of 0.02 mm occurred in vertical load test with a loading of 18 tonnes at first replication. In this combination, there was also a stress of 7 N/mm². The highest strain experienced by NT-60 bogie was 0.21 mm in the horizontal load with a loading of 20 tonnes at first replication. In this condition, a stress of 44.1 N/mm² occurred.